Sardar Patel: the cartographer of modern India - Kurhade, M.S. (University News)
(3z(BI make earnest appeals to people to wipe out from their minds and memories of the post treating it as a terrible nightmare, and look forward with single mined purpose to make India, strong, prosperous and happy. This can only be done by hard work.(3y(B- Reproduced s